Construction and Operation of Small Hydro Power Plants in the Ukrainian Carpathians: New Challenges for Environment - Pylypovych, O. V.; Ivanov, E. A.; Mykitchak, T. I.; Shtupun, V. P. (Man and Environment. Issues of Neoecology, 2020)
Purpose. Analysis of environmental problems and risks associated with the construction and operation of small hydroelectric power facilities (SHEPP) in the Ukrainian Carpathians.Methods. Field studies, statistical, hydrological, hydroecological, analysis and synthesis.Results. Potential environmental risks arising from the construction and operation of SHEPP in the Ukrainian Carpathians are considered. The influence of Yavіrska hydroelectric power station on water discharges in the Stryi river was investigated. The daily water discharges for the two hydraulic sections located above and below the station for low-water (2003) and high-water (2008) years are analyzed. Possible risks in the construction and operation of the hydroelectric power plant for the movement of flood waters, river sediments, the development of riverbed deformations, and others, are indicated. The difference in water discharges between the two hydrological stations is presented, and it is confirmed that in the spring of 2008 and 2003 and the autumn and winter of 2003 and 2008 minimal differences in water consumption were observed as a result of the water retention in the reservoir above the dam of Yavіrska hydro power station for the maximal electrical power generation. The impact of the Yavіrska SHEPP on the biota of the Stryi river during 2014–2015 was analyzed. The obtained results indicate that the main negative factors affecting the communities of river hydrobionts are the creation of reservoir of limnethic conditions in the continuum of the river ecosystem; the accumulation of sediments and dead organic matter on its bottom and banks and the demolition of these sediments on the lower sections of the channel bed; also a decrease of water in the riverbed downstream of the dam after the closure of the floodgates in June. The analysis of the environmental impact assessment reports made it possible to analyze the major environmental threats, which are possible during the building and operation of a small hydroelectric power plant on the Stryi river in the Dovhe village (Drohobych district, Lviv region).Conclusions. To prevent the impact of the projected SHEPP in the Carpathian region it is necessary to prescribe the mechanism of carrying out the environmental impact assessment, to specify the natural-geographical, hydrological and hydro-ecological restrictions on the construction and operation of the hydroelectric power station. It is also necessary to identify sections of mountain (“wild”) rivers with high values of natural landscapes and prohibit the construction of small hydropower facilities.